Flavonoid diversity and roles in the Lipopolysaccharide mediated inflammatory response of Monocytes and Macrophages - Rullah, Kamal; Shamsudin, Nur Farisya; Koeberle, Andreas; Tham, Chau Ling; Mohd Aluwi, Mohd Fadhlizil Fasihi; Leong, Sze Wei; Jantan, Ibrahim; Lam, Kok Wai (Taylor & Francis, 2024)
Targeting lipopolysaccharide (LPS)/toll-like receptor 4 signaling in mononuclear phagocytes has been explored for the treatment of inflammation and inflammation-related disorders. However, only a few key targets have been translated into clinical applications. Flavonoids, a class of ubiquitous plant secondary metabolites, possess a privileged scaffold which serves as a valuable template for designing pharmacologically active compounds directed against diseases with inflammatory components. This perspective provides a general overview of the diversity of flavonoids and their multifaceted mechanisms that interfere with LPS-induced signaling in monocytes and macrophages. Focus is placed on flavonoids targeting MD-2, IκB kinases, c-Jun N-terminal kinases, extracellular signal-regulated kinase, p38 MAPK and PI3K/Akt or modulating LPS-related gene expression.